2020
DOI: 10.1155/2020/8822686
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Penetration Effort in an Artificial Tissue by Hypodermic Needles

Abstract: Fear of injection-related pain is a drawback to injectable therapy. Hypodermic injections are a cause for great anxiety and reduced adherence to the subcutaneous application of insulin for glycemic control in diabetics or in the treatment of multiple sclerosis, increasing the risk of complications and mortality. Injured or sick people have to undergo several daily injections, forcing them to rotate the veins and regions used to recover from the trauma caused by the perforation of the skin, tissue, muscles, vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…When accounting for needle gauge and bevel angle, the forces required to penetrate human cornea and corneoscleral limbus tissues are 282 and 382 mN, respectively. [34,35] These forces are similar to the penetration force we experimentally derived for rabbit tissues (364.9 mN), demonstrating that the MagnetoSuture system is capable of clinical corneal penetration and intravitreal injections. This mechanism offers an important potential route of force magnification for suturing and other needle-based interventions in clinically relevant settings, where repetitive mechanical penetration is required.…”
Section: Discussionsupporting
confidence: 75%
“…When accounting for needle gauge and bevel angle, the forces required to penetrate human cornea and corneoscleral limbus tissues are 282 and 382 mN, respectively. [34,35] These forces are similar to the penetration force we experimentally derived for rabbit tissues (364.9 mN), demonstrating that the MagnetoSuture system is capable of clinical corneal penetration and intravitreal injections. This mechanism offers an important potential route of force magnification for suturing and other needle-based interventions in clinically relevant settings, where repetitive mechanical penetration is required.…”
Section: Discussionsupporting
confidence: 75%
“…At one end, there is a chamfer called a bevel. This is the tip of the needle and is designed to facilitate tissue perforation (see Figure 3) [52]. Comparative analyses were performed to understand the influence of some coating variables on the penetration effort, such as the silica nanoparticles content in the acrylic polymer pastes and the number of coating layers.…”
Section: Resultsmentioning
confidence: 99%
“…In this condition: 13.63% of silica nanoparticles in the acrylic polymer paste, probably the number of nanoparticles will determine the curve behavior of viscosity. 52 The shear stress versus shear rate data (see Figure 5) for all blends in the range of 0.01 to 800 s �1 , were best fitted to the power-law model, equation ( 4), this model is extensively used to describe the flow properties of non-Newtonian fluids [48,50]. As shown in Figure 4, all blends exhibited pseudoplastic behavior.…”
Section: Rheological Properties Of Coating Solutionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Currently, many medical devices are manufactured with polymer materials, and silicone oil has been used to improve the performance of polymer-based medical devices. Silicone oil is the liquid form of silicones (polysiloxane), and silicones have been used to manufacture contact lenses, cannulas, catheters, implants, wound dressing, cosmetics, biomedical lubricants, and so on. Silicone oil is also used to create the slippery interfaces between medical devices and the exterior physiological environment, providing lubricant layers on medical devices including syringe needles, cannulas, catheters, and intranasal splints. It is reported that silicone oil lubricated polymer syringes showed enhanced physical stability during the shipping and handling of biopharmaceuticals . Silicone-based interfaces have also been fabricated by infusing silicone oil onto silicone-based materials to form a slippery liquid infused porous surface (SLIPs).…”
Section: Introductionmentioning
confidence: 99%